Structure Diversity Assessment of Native Chicken Population of North Gujarat by Hardy Weinberg Equilibrium Test and Bottleneck Analysis - Chaudhary, Dhavalkumar F; Dave, Ankit; Mankad, Pooja; Patel, Dinesh; Patel , Ashish C; Joshi, Rajesh S (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Genetic characterization evaluates the population's genetic homogeneity, heterogeneity, inbreeding or introgression. The evolutionary history of a species or breed and/or population is revealed through the phylogenetic relationships between populations based on microsatellite analysis. Even the status of the breeds in the specified geographic area can be monitored to prioritize the breed’s conservation. Based on this a desi/native chicken population reared by tribal communities from North Gujarat were characterized by 25 microsatellite markers on 60 chicken blood samples. The microsatellites were amplified in seven multiplex panels using fluorescently labelled primers and genotyped on genetic analyzer system. In results, only five microsatellites were found to be in Hardy-Weinberg Equilibrium (HWE). Rest of the microsatellite loci deviated significantly (p
Keywords: Bottleneck analysis; Bottleneck analysis Genetic characterization; Native chicken of Gujarat